“A Golden Thread”: the Concept for Development of Nerchinsk Historical Center - Repina, Anastasia; Sokolov, Stanislav; Kholyavko, Anastasia (project baikal, 2019)
“A Golden Thread”, a concept for development and improvement of Nerchinsk historical center, was worked out for participation in the All-Russian competition of the best projects for a comfortable urban environment “Small Towns and Historic Settlements”. The concept is a part of the project for complex reconstruction of the center “Golden Capital of Dauria”, as well as the project for strategic development of the city “Historical Nerchinsk”. The tourist route will connect central architectural landmarks and event venues. The landmarks included in the route were mostly chosen as growing points for the city’s economy and involvement of residents in development of spaces.
Keywords: small towns and historic settlements; Nerchinsk; Golden Capital of Dauria; tourist route; participative design